2010
DOI: 10.1128/jb.00860-09
|View full text |Cite
|
Sign up to set email alerts
|

Polar Positioning of a Conjugation Protein from the Integrative and Conjugative Element ICEBs1ofBacillus subtilis

Abstract: ICEBs1 is an integrative and conjugative element found in the chromosome of Bacillus subtilis. ICEBs1 encodes functions needed for its excision and transfer to recipient cells. We found that the ICEBs1 gene conE (formerly yddE) is required for conjugation and that conjugative transfer of ICEBs1 requires a conserved ATPase motif of ConE. ConE belongs to the HerA/FtsK superfamily of ATPases, which includes the wellcharacterized proteins FtsK, SpoIIIE, VirB4, and VirD4. We found that a ConE-GFP (green fluorescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(73 citation statements)
references
References 56 publications
2
69
2
Order By: Relevance
“…Most of the predicted or experimentally demonstrated transfer proteins encoded by ICEBs1 have homologs encoded by conjugative plasmids found in the Firmicutes. Four of these proteins are homologous to VirB1, VirB4, VirB11, and VirD4 proteins, which belong to inner membrane part of the T4SS of conjugative plasmids found in Gram-negative bacteria (72,73,74). Interestingly, the genes encoding the site-specific recombination functions and allowing intracellular mobility of ICEBs1 are not grouped in the same region.…”
Section: Genetic Organizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the predicted or experimentally demonstrated transfer proteins encoded by ICEBs1 have homologs encoded by conjugative plasmids found in the Firmicutes. Four of these proteins are homologous to VirB1, VirB4, VirB11, and VirD4 proteins, which belong to inner membrane part of the T4SS of conjugative plasmids found in Gram-negative bacteria (72,73,74). Interestingly, the genes encoding the site-specific recombination functions and allowing intracellular mobility of ICEBs1 are not grouped in the same region.…”
Section: Genetic Organizationmentioning
confidence: 99%
“…Several observations suggested that ICEBs1 was capable of extrachromosomal replication, such as the relative stability of a ΔimmR mutant and the relocalization of the replisome during ICEBs1 conjugative transfer (72,78). Further studies led to a precise model of RC replication of the activated extrachromosomal circular form of ICEBs1 (98).…”
Section: Replication Of Icebs1mentioning
confidence: 99%
See 1 more Smart Citation
“…In strain 2603V/R, IS1381 interrupts a gene (sag2004/sag2001) predicted to encode a conjugal transfer protein belonging to the ConE/YddE family (Tettelin et al, 2002). In Bacillus subtilis, ConE is an ATPase of the FtsK/HerA superfamily that is required for the conjugative transfer of ICEBs1 (Berkmen et al, 2010). This suggests that IS1381 might be involved in the regulation of horizontal gene transfer.…”
Section: Mobile Genetic Element Of the Is5 Familymentioning
confidence: 99%
“…1A). In the receiving cell, the ICE must ensure effective integration to avoid being lost upon cell division because of its limited selfreplication capacity (22,23) (Fig. 1B).…”
mentioning
confidence: 99%